Pengaruh Ukuran Perusahaan, Struktur Modal, Dan Profitabilitas Terhadap Nilai Perusahaan Pada Pt. Semen Indonesia Tbk Periode 2014 - 2023 - Fazli, Winari Nida; Priyanto, Aria Aji (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study seeks to assess the impact of firm size, capital structure, and profitability on the corporate value of Semen Indonesia Tbk from 2014 to 2023. This study employs a quantitative methodology, analyzing financial statement data from firms registered on the Indonesia Stock Exchange (IDX). The data analysis techniques utilized encompass descriptive statistical analysis, classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation tests), multiple linear regression analysis, hypothesis testing (T-test and F-test), and the coefficient of determination, all performed using SPSS (Statistical Package for the Social Sciences) software, version 26. The results of this research indicate that, partially, company size does not have a significant effect on company value, as shown by tcount < ttable, namely -2,323 < 2,447, with a significance value of 0,059 > 0,05. Conversely, partially, capital structure has a significant effect on company value, with tcount > ttable, namely 3,315 > 2,447, and a significance value of 0,016 < 0,05. Partially, profitability does not have a significant effect on company value, as evidenced by tcount < ttable, namely 2,103 < 2,447, with a significance value of 0,080 > 0,05. Simultaneously, company size, capital structure, and profitability have a significant effect on company value, as indicated by fcount > ftable, namely 15,294 > 4,35, with a significance value of 0,003 < 0,05.